„Godne pochwały jest rozgłaszać i wysławiać dzieła Boże”. Znaczenie czynu ('ergon') w Starym Testamencie - Nawracała, Tomasz (Wydawnictwo Gaudentinum, 2015)
A human being in his/her entire existence is oriented towards God. Thanks to His grace, not only is he/she ‘capax Dei’, but only in God does he/she feel fulfilled. Eternity is the communion of people and man has been invited to it. He/she enters it after the Final Judgement, delivered by God after a person’s death. What will the result of the Final Judgement be? Who and what will survive it? The man deprived of everything or his/her deeds, as well? These were deeds thanks to which he/she achieved salvation, and thus it is possible that they will be preserved in God. This article aims at answering the question of what deeds can be preserved in eternity according to the authors of the Old Testament.
It is right to reveal and publish the works of God. The significance of deed (ergon) in the Old Testament
Keywords: wieczność; ergon; czyn; odpłata; nagroda; kara; eternity; deed; payment; reward; punishment